Effect of phosphorus and aluminum levels on spike structures of wheat - Zanatta, Ana Christina Albuquerque; Mundstock, Claudio Mário (Pesquisa Agropecuaria Brasileira, 1991)
Two wheat cultivars, CNT 10 and PAT 7392, were grown under two phosphorus levels (40 and 160 ppm of P2O5) and four lime levels (0, 1/4, 1/2 and 1 SMP). Plants were grown in greenhouse until elongation and then transferred to phitotron until mealy ripe grains. Spikes structures were evaluated in the main tiller of each plant. PAT 7392 showed higher dry matter yield potential (straw and grains) and converted it more efficiently into grains, while CNT 10 into vegetative structures.